2021
DOI: 10.1177/01937235211012171
|View full text |Cite
|
Sign up to set email alerts
|

Feminist Sociology Confluences With Sport Science: Insights, Contradictions, and Silences in Interviewing Elite Women Athletes About Low Energy Availability

Abstract: This article explores the socio-cultural dimensions of elite sportswomen’s experiences of low energy availability (LEA), focusing particularly on elite track cyclists. With a multidisciplinary research team (two sport scientists and a feminist sociologist), the project began with a suite of quantitative measures that identified five of eight women track cycling athletes categorized with LEA and three athletes categorized with sub-optimal energy availability. This was then followed by semi-structured interviews… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…As discussed earlier, while medical anxieties often constructed women's bodies to exclude them from political, social, and sporting spaces (Verbrugge, 2002; Vertinsky, 1990), there also exist physical risks. Amenorrhea (the absence of menstruation), for example, has been linked to low energy availability—a consequence of insufficient dietary intake—and other destructive behaviours, such as disordered eating and osteoporosis (De Souza et al, 2014; Schofield et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As discussed earlier, while medical anxieties often constructed women's bodies to exclude them from political, social, and sporting spaces (Verbrugge, 2002; Vertinsky, 1990), there also exist physical risks. Amenorrhea (the absence of menstruation), for example, has been linked to low energy availability—a consequence of insufficient dietary intake—and other destructive behaviours, such as disordered eating and osteoporosis (De Souza et al, 2014; Schofield et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Though dominantly focusing on prevention, diagnosis, and treatment options, scientists also indicate the unique social pressures for girls and women, which include coaching pressures and associating unrealistically thin bodies with success (De Souza et al, 2014). Extending into social science fields, feminist sociologists have explored the entangled biological and psychosocial dimensions of women's health, experiences, and bodies, particularly in the case of RED-S (see Schofield et al, 2021; Thorpe, 2016).…”
Section: Situating Protective Policies For Women Athletesmentioning
confidence: 99%
“…Building more supportive, inclusive, and equitable environments for the health and wellbeing of women and gender expansive people further requires gender-responsive approaches that promote broader cultural change. Feminist sport and exercise medicine practitioners, sports scientists, and social science researchers are increasingly coming together in their efforts to engage in inter-and transdisciplinary work on a range of topics, including gendered approaches to sports injury (7), menstrual health (8), Relative Energy Deficiency in Sport (9)(10)(11) and research design in exercise and sport science (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…Through her work with WHISPA, she has organized three national symposiums focused on women's health and wellbeing in sport, collaborated with sports doctors, physiologists, psychologists, nutritionists and endocrinologists on research relating to women athlete health in Aotearoa ( 8 ) and co-produced an array of educational materials for coaches, athletes and parents (see https://hpsnz.org.nz/home/whispa-healthy-women-in-sport-a-performance-advantage/ ). She has also written on the theoretical and methodological complexities of such transdisciplinary research and practice ( 10 , 11 , 18 ), and the importance of localized and cultural ways of knowing health and wellbeing in elite sport ( 19 ). Sheree (she/her) was born in South Africa, grew up in Botswana, completed her PhD in Australia, and now calls Bath (United Kingdom) home.…”
Section: Introductionmentioning
confidence: 99%
“…Despite this evidence regarding the impact of maladaptive cognitions and emotions upon eating and exercise behaviours, recent qualitative studies have suggested that athletes who have recovered, or are recovering, from RED-S can be aware of the detrimental health implications of the condition, yet still possessing a desire to achieve or maintain a lean physique or low body mass, which can undermine their efforts to achieve optimal EA (Langbein et a1., 2021;Thorpe & Clark, 2020). In a mixed-methods study of elite female cyclists, Schofield et al (2021) reported that some athletes with sub-optimal EA and LEA may acknowledge the importance of adequate EA for physiological adaptations and performance improvements (e.g., improved muscle mass and strength), but simultaneously need to contend with internal and external pressures to avoid increasing fat mass or overall body mass. Similarly, Stoyel et al (2021) recently highlighted how elite male and female endurance athletes who internalise the conflicting beliefs and expectations of society (i.e., food is to be enjoyed and embraced as central to social connection) and the sporting domain (i.e., an athlete's eating behaviours should reflect their dedication to their sport) may engage in DE behaviour to strike a balance between these competing demands.…”
Section: Introductionmentioning
confidence: 99%